8 - An Empirical Profile of Weak States in Sub-Saharan Africa: 10.4314/ad.v28i2.22181 - Atiku-Abubakar, Jennifer J.; Shaw-Taylor, Yoku (Africa Development, 2003)
In this paper, we present an empirical construct to describe attributes of weak states in sub-Saharan Africa using the Minorities at Risk Database. Weak states are defined as having a prevalence of structural inequality, the components of which are economic differentiation, cultural (or social) inequality and political inequality. We used this construct to predict intercommunal conflict in two peri ods: between 1940 and 1989, and since 1990. Analysis showed that the struc tural inequality construct is reliable and that the likelihood of intercommunal conflict between 1940 and 1989 was associated with cultural differentials. Results also suggest that structural inequality, by itself, does not directly lead to intercommunal conflict. We argue that the addition of a variable that captures prevalence of small arms or light weapons will improve the predictive power of the model. Frequency distributions of the construct revealed that there is a high incidence of intercommunal conflict in the region and that three countries in particular were 'best performers'.